Design and Control of a Two Switch Forward Converter with Supertwisting Sliding Mode - Kayisli, Korhan; Caglayan, Ruhi Zafer; Coteli, Resul; Roscia, Mariacristina; Harrouz, Abdelkader; Belkaid, Abdelhakim (Ieee, 2024)
This paper presents the design and control of a two-switch forward converter utilizing a supertwisting sliding mode control (STSMC) strategy. The two-switch forward converter, known for its efficiency in medium-power applications, is equipped with a robust control method to ensure improved stability and dynamic performance under varying operating conditions. The supertwisting sliding mode approach is chosen for its ability to mitigate chattering effects, a common drawback in traditional sliding mode control, while ensuring precise tracking and disturbance rejection. Through comprehensive simulation, the proposed system demonstrates enhanced performance in terms of voltage regulation and improved transient response. The results indicate that the integration of STSMC significantly improves the converter's efficiency and robustness, making it suitable for various power conversion applications.
13th International Conference on Renewable Energy Research and Applications -- NOV 09-13, 2024 -- Nagasaki, JAPAN
Keywords: Supertwisting; Sliding Mode; Two Switch Forward Converter; Robust Control